2018
DOI: 10.25159/2520-5293/3901
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Intensive Care Nurses Regarding the Monitoring of Early Enteral Nutrition

Abstract: Early initiated and uninterrupted enteral nutrition is associated with the reduction of disease severity, diminished complications, decreased hospital length of stay, and favourably affects the outcomes of critically ill patients. The aim of the study was to assess the knowledge of early enteral nutrition (EEN) monitoring among intensive care unit (ICU) nurses in selected facilities in the Eastern Cape, South Africa. A quantitative, descriptive and cross-sectional design was followed. A total of 115 questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
0
2
Order By: Relevance
“…The results are consistent with those of Penland 30 in relation to the respondents’ age, as the researcher reported that the respondents’ knowledge level was not significantly associated with age. However, our results are in disagreement with the results of studies by Taha and Said 16 and Mooi 31 in relation to the nurses’ age and years of working experience, as the researchers found that there was a highly statistically significant association between knowledge level regarding EN care and the respondents' age and previous working experience. This discrepancy might be attributed to the nature of training courses provided and the differences in the respondents' data, where it was found that young and newly graduated nurses had been more receptive, more tolerant and have a more potent memory.…”
Section: Discussioncontrasting
confidence: 99%
“…The results are consistent with those of Penland 30 in relation to the respondents’ age, as the researcher reported that the respondents’ knowledge level was not significantly associated with age. However, our results are in disagreement with the results of studies by Taha and Said 16 and Mooi 31 in relation to the nurses’ age and years of working experience, as the researchers found that there was a highly statistically significant association between knowledge level regarding EN care and the respondents' age and previous working experience. This discrepancy might be attributed to the nature of training courses provided and the differences in the respondents' data, where it was found that young and newly graduated nurses had been more receptive, more tolerant and have a more potent memory.…”
Section: Discussioncontrasting
confidence: 99%
“…The results are consistent with those of Penland 29 in relation to the respondents' age, as the researcher reported that the respondents' knowledge level was not significantly associated with age. However, our results are in disagreement with the results of studies by Taha and Said 16 and Mooi 30 in relation to the nurses' age and years of working experience, as the researchers found that there was a highly statistically significant association between knowledge level regarding EN management and the respondents' age and previous working experience. This discrepancy might be attributed to the nature of training courses provided and the differences in the respondents' data, where it was found that young and newly graduated nurses had been more receptive, more tolerant and have a more potent memory.…”
Section: Discussioncontrasting
confidence: 99%